Regulating droplet impact symmetry by surface engineering. Issue 2 (16th March 2023) - Zhao, Zhipeng; Li, Huizeng; Liu, Quan; Li, An; Xue, Luanluan; Yuan, Renxuan; Yu, Xinye; Li, Rujun; Deng, Xiao; Song, Yanlin
Abstract: Droplet impact on solid surfaces is essential both in nature and industry. Precisely regulating the dynamic behavior of droplet impact is of great significance for energy harvesting, anti‐icing, inkjet printing, pesticide spraying, and many other fields. Various rebounding behaviors (deposition, rebounding, rotation, instability control, and so on) and rebounding intrinsic parameters (such as contact time) after droplets impacting on solid surfaces can be regulated by surface engineering. This paper reviews the advances in regulating droplet impact behavior from the perspective of symmetry by modifying solid surfaces from the following aspects: chemical modification and physical structure regulation, in which the symmetry is discussed from mirror symmetry and rotational symmetry. Firstly, the symmetry of the droplet impact dynamics and its influencing factors are introduced. Then the modulation of droplet impact symmetry, using homogeneous and heterogeneous chemically modified solid surfaces, is summarized. The following presents the influence of physical structures, from micro to macro scale compared to the droplet size, on the droplet impact symmetry. Finally, the future challenges and opportunities of the droplet impact behavior regulation are discussed. Abstract : Droplet impact on solid surfaces is essential both in nature and industry. This paper reviews the advances in regulating droplet impact behavior from the perspective of symmetry by modifying solid surfaces from the following aspects: chemical modification and physical structure regulation, in which the symmetry is discussed from mirror symmetry and rotational symmetry.